PENGELOLAAN MANGROVE SEBAGAI PELINDUNG KAWASAN PESISIR DENGAN PENDEKATAN CO-MANAGEMENT DAN ANALYSIS HIERARCHY PROCESS (AHP) (Studi di Kabupaten Pemalang, Jawa Tengah) - Sutanto, Himawan Arif (PRESTASI, 2010)
This research is aim to analyse mangrove management in Pemalang regency as the coastal area protector and priority that need to be implemented in good management. The quota sampling used to obtained the number of samples in this research. There are 132 people has participated as the responders consisted of 100 head of household and 32 key-persons. Co-management approach has been applied to determine the sharing of responsibility in mangrove management and Analysis Hierarchy Process (AHP) applied to determine priority in good management of mangrove.The results of this study indicated that most of people living at coastal area in Pemalang regency is a fishpond farmer which can affect in decreasing environmental in coastal area if it is not managed in correct. The community involvement of mangrove management still less although has been formed care coastal area group but still relying on project from the Government either National and Local. Execution prospect of co-management in mangrove management of Pemalang regency is fairly good. It is indicated by the existence of fisher groups and the existence support from government and by international NGO such as OISCA (Japan) and Wet Land (Dutch).Keyword:         Co-management, Analysis Hierarchy Process, Mangrove, Coastal Are, Pemalang